Self-determined, but not non-self-determined, motivation predicts activations in the anterior insular cortex: an fMRI study of personal agency - Lee, Woogul (Oxford University Press, 2013)
Neuroscientific studies on agency focus rather exclusively on the notion of who initiates and regulates actions, not on the notion of why the person does. The present study focused on the latter to investigate two different reasons underlying personal agency. Using event-related functional magnetic resonance imaging, we scanned 16 healthy human subjects while they imagined the enactment of volitional, agentic behavior on the same task but either for a self-determined and intrinsically motivated reason or for a non-self-determined and extrinsically motivated reason. Results showed that the anterior insular cortex (AIC), known to be related to the sense of agency, was more activated during self-determined behavior while the angular gyrus, known to be related to the sense of loss of agency, was more activated during non-self-determined behavior. Furthermore, AIC activities during self-determined behavior correlated highly with participants’ self-reported intrinsic satisfactions. We conclude that self-determined behavior is more agentic than is non-self-determined behavior and that personal agency arises only during self-determined, intrinsically motivated action.